ZFTA-RELA dictates oncogenic transcriptional programs to drive aggressive supratentorial ependymoma - Arabzade, Amir; Zhao, Yanhua; Varadharajan, Srinidhi; Chen, Hsiao-Chi; Jessa, Selin; Rivas, Bryan; Stuckert, Austin J.; Solis, Minerva; Kardian, Alisha; Tlais, Dana; Golbourn, Brian J.; Stanton, Ann-Catherine J.; et al. (Cancer discovery, 2021)
More than 60% of supratentorial ependymomas harbor a ZFTA-RELA (ZRfus) gene fusion (formerly C11orf95-RELA). To study the biology of ZRfus, we developed an autochthonous mouse tumor model using in utero electroporation (IUE) of the embryonic mouse brain. Integrative epigenomic and transcriptomic mapping was performed on IUE-driven ZRfus tumors by CUT&RUN, chromatin immunoprecipitation sequencing, assay for transposase-accessible chromatin sequencing, and RNA sequencing and compared with human ZRfus-driven ependymoma. In addition to direct canonical NFκB pathway activation, ZRfus dictates a neoplastic transcriptional program and binds to thousands of unique sites across the genome that are enriched with PLAGL family transcription factor (TF) motifs. ZRfus activates gene expression programs through recruitment of transcriptional coactivators (Brd4, Ep300, Cbp, Pol2) that are amenable to pharmacologic inhibition. Downstream ZRfus target genes converge on developmental programs marked by PLAGL TF proteins, and activate neoplastic programs enriched in Mapk, focal adhesion, and gene imprinting networks. - Significance: Ependymomas are aggressive brain tumors. Although drivers of supratentorial ependymoma (ZFTA- and YAP1-associated gene fusions) have been discovered, their functions remain unclear. Our study investigates the biology of ZFTA-RELA-driven ependymoma, specifically mechanisms of transcriptional deregulation and direct downstream gene networks that may be leveraged for potential therapeutic testing.
Gesehen am 28.10.2021